The Views of Ex-Police Officers on Child Abuse Case Attrition in the United Kingdom - Krahenbuhl, Sarah J. (Journal of interpersonal violence, 2021)
Attrition in child abuse cases is of continuing concern. International research has produced evidence to suggest that the form and quality of the evidence available in many child abuse cases is of insufficient quality to allow progression through the judicial system. Recent revelations have led to an increase in public and professional awareness of the prevalence of child sexual abuse, and how this is managed by the legal and social care systems. The aim of this research was to explore the opinions of ex-Police Officers who had direct experience relating to the management of child abuse cases about the factors affecting case progression. Seven ex-Police Officers were interviewed and the transcribed data were thematically analyzed. The five main themes derived from the data were Global Myths, Assumptions, and Misconceptions; Suitability; Resources; Professionals’ Attributes; and Working Together. These themes demonstrated that the primary issues indicated by ex-Police Officers were more about relationships between professionals, an understanding of the child’s perspective, and their subsequent involvement in the legal processes than simply being related to a lack of resources.